Women, Patronage, and Self-Representation in Islamic Societies: By Ruggles Fairchild (editor), Albany: State University of New York Press, 2000. (American Journal of Islam and Society, 2001)
The aim of the authors in this book was to provide a supplementary text for studieson gender issues in Islamic societies. Ruggles Fairchild (editor) notes that amore significant aim of the book was to broaden not only the geographical realmbut the scope and the time frame of analysis of the studies on gender in Islamicsocieties. This book examines the implicit economic, social and political influenceof elite Muslim women in their respective societies by shedding light on thewomen's patronage of architecture, clothing and art. Authors argue that suchvisible expressions - products of women who were otherwise invisible in society -were, and are, reflective of women's implicit agency (means of exerting power insociety) in ancient Islamic societies. The main premise of the authors is that whilewomen have been absent in the explicit representation (depiction) of art,architecture and society, they have in fact been very much present in thebackground of these realms of Islamic society.While other studies of gender have emerged from consideration of social,economic and political structures in Muslim societies, few (if at all, argue theauthors) have emerged from an examination of "visual arts" or "visual culture" (p.2). This is the void the book seeks to fill. In this sense this book is very important,as it sheds light on the subtle agency of women in ancient Islamic societies andchallenges the stereotypical notion that women were (are) subservient, mutedentities in Islamic societies (past or present). In their challenge of the stereotypicalview of Muslim women in ancient Islamic societies, the authors also question the ...